Implementasi 3D Object Tracking Pada Kamus Benda Dalam Bahasa Inggris Berbasis Augmented Reality - mursalim mursalim; Risaldi Risaldi; Butsiarah Butsiarah; tamra tamra (LLDikti Wilayah IX Sulawesi dan Gorontalo, 2021)
This study aims to design and implement a 3D Object Tracking application on an Augmented Reality-based object dictionary using the Markerless method and the Vuforia database. The results of this study indicate that an English learning support system can be implemented for elementary school students to provide convenience in learning English both in pronunciation and writing of object names in English by utilizing Augmented Realty for shape recognition of object names with a percentage result 81 ,72% of Usibility testing.